Selective and direct hydrogen generation from mixed plastic waste via alkaline thermal treatment with inherent carbon storage - Jieun Park; Hyunah Kim; Hyerin Seo; Jiwon Lee; Hyung-Kyu Lim; Wonho Jung; Ah-Hyung Alissa Park; Woo-Jae Kim (Proceedings of the National Academy of Sciences, 2026)
The global accumulation of plastic waste has spurred extensive research into chemical recycling methods to mitigate environmental issues and convert waste into valuable resources. A major challenge in plastic recycling is the requirement for presorting, which complicates processing and increases costs. Here, we demonstrate alkaline thermal treatment (ATT) as a highly efficient strategy for directly converting mixed plastic waste, including polyethylene terephthalate (PET), polyethylene (PE), and polypropylene (PP), into clean hydrogen energy at low temperatures and atmospheric pressure. Unlike conventional gasification, NaOH-assisted ATT enables plastic decomposition at significantly lower temperatures while producing high-purity hydrogen and minimizing carbon emissions. A key advancement in this work is the oxidation pretreatment of PP and PE, which enhances their reactivity in ATT and allows efficient hydrogen generation even from typically resistant polyolefins. Through systematic optimization of the NaOH-to-plastic ratio and thermal oxidation conditions, hydrogen yields of 43.7, 51.9, and 30.2 mmol/g plastic were achieved for PET, PE, and PP, respectively. Furthermore, ATT efficiently converts both individual and mixed plastic waste without requiring extensive separation, demonstrating its commercial potential and scalability with real-world waste compositions. Overall, this study establishes ATT as a promising and sustainable solution for plastic waste management and clean energy production, providing an economically viable low-carbon pathway for hydrogen generation.